2018
DOI: 10.1016/j.dadm.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate metabolic imaging marker for behavioral variant frontotemporal dementia

Abstract: Introduction The heterogeneity of behavioral variant frontotemporal dementia (bvFTD) calls for multivariate imaging biomarkers. Methods We studied a total of 148 dementia patients from the Feinstein Institute (Center-A: 25 bvFTD and 10 Alzheimer's disease), Technical University of Munich (Center-B: 44 bvFTD and 29 FTD language variants), and Alzheimer's Disease Neuroimaging Initiative (40 Alzheimer's disease subjects). To identify the covariance pattern of bvFTD (behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
(104 reference statements)
2
17
1
Order By: Relevance
“…Studies that have utilized pattern classification techniques have found that structural MRI can differentiate bvFTD from controls with an accuracy of 85% 85,86 , and differentiate bvFTD from Alzheimer's dementia with an accuracy of 82% 86 . Diagnostic accuracy has also been shown to be excellent with pattern analysis of FDG-PET, with discriminatory power of 92.2% to differentiate bvFTD from Alzheimer's dementia and 87.6% to differentiate bvFTD from the other language variants of FTD 87 . In fact, simple visual assessments of FDG-PET looking for frontal, anterior cingulate and anterior temporal hypometabolism have excellent specificity (97.6%) and sensitivity (86%) in differentiating bvFTD from Alzheimer's dementia, and can improve differentiation based on clinical features alone 88 .…”
Section: Imaging In the Clinical Syndromes Of Ftd Behavioral Variant Ftdmentioning
confidence: 99%
“…Studies that have utilized pattern classification techniques have found that structural MRI can differentiate bvFTD from controls with an accuracy of 85% 85,86 , and differentiate bvFTD from Alzheimer's dementia with an accuracy of 82% 86 . Diagnostic accuracy has also been shown to be excellent with pattern analysis of FDG-PET, with discriminatory power of 92.2% to differentiate bvFTD from Alzheimer's dementia and 87.6% to differentiate bvFTD from the other language variants of FTD 87 . In fact, simple visual assessments of FDG-PET looking for frontal, anterior cingulate and anterior temporal hypometabolism have excellent specificity (97.6%) and sensitivity (86%) in differentiating bvFTD from Alzheimer's dementia, and can improve differentiation based on clinical features alone 88 .…”
Section: Imaging In the Clinical Syndromes Of Ftd Behavioral Variant Ftdmentioning
confidence: 99%
“…These patterns with numerical expressions help the differential diagnosis, the evaluation of disease severity, and tracking therapy response [21]. The bv‐FTD‐related pattern scores successfully distinguished bv‐FTD from AD, FTD language variants (sv‐PPA and nfv‐PPA), and controls, although the authors did not identify the differential diagnostic efficacy respectively between bv‐FTD and sv‐PPA or nfv‐PPA [22]. This study aimed to establish an sv‐PPA‐related pattern (sv‐PPARP) using PCA and evaluate its potential in differential diagnosis and disease severity assessment.…”
Section: Introductionmentioning
confidence: 99%
“…PET with 18 F-FDG is an established clinical tool for early and differential diagnosis of dementing and movement disorders (9,10). Although multivariate decomposition of PET data has been successfully applied in both neurodegenerative dementia (11) and Parkinsonian syndromes (12), RSNs could be identified in 18 F-FDG PET data only recently (13)(14)(15)(16). In particular, our group has found spatially similar RSNs in fMRI and 18 F-FDG PET data in the same group of healthy subjects (15).…”
mentioning
confidence: 82%